2006
DOI: 10.1086/501499
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Large‐Scale Structures of Astrophysical Jets in the Magnetically Dominated Limit

Abstract: We suggest a new approach that could be used for modeling both the large-scale behavior of astrophysical jets and the magnetically dominated explosions in astrophysics. We describe a method for modeling the injection of magnetic fields and their subsequent evolution in a regime where the free energy is magnetically dominated. The injected magnetic fields, along with their associated currents, have both poloidal and toroidal components, and they are not force free. The dynamic expansion driven by the Lorentz fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(150 citation statements)
references
References 22 publications
10
139
1
Order By: Relevance
“…The magnitude of ∼ 10 18 ampères for the electric current associated with a 10 8 M BH, was originally predicted by Lovelace (1976). It is integral to the simulations of Li et al (2006) in Figure 3, and now tentatively confirmed in an actual measurement in (by Kronberg in Ji et al, 2008) as discussed above. Another success of this class of model is that the current-driven instabilities are more able than hydrodynamic, e.g.…”
Section: Poynting Flux Jetssupporting
confidence: 71%
See 1 more Smart Citation
“…The magnitude of ∼ 10 18 ampères for the electric current associated with a 10 8 M BH, was originally predicted by Lovelace (1976). It is integral to the simulations of Li et al (2006) in Figure 3, and now tentatively confirmed in an actual measurement in (by Kronberg in Ji et al, 2008) as discussed above. Another success of this class of model is that the current-driven instabilities are more able than hydrodynamic, e.g.…”
Section: Poynting Flux Jetssupporting
confidence: 71%
“…Indeed RM ≈ 0 within measurement errors after subtracting the smoothed RM of nearby background at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S1743921309031172 502 P. P. Kronberg The helical structure of a simulated "magnetic tower" poynting flux jet, after Li et al (2006). Right: Simulated current structure of a combined magnetic tower poynting flux jet + lobe system (Nakamura et al, 2008). sources.…”
Section: First Assumption-free Measurement Of An Extragalactic Jet Cumentioning
confidence: 99%
“…Recent observations [2] have demonstrated that the MHD kink instability occurs in solar flux ropes which can disrupt yielding twisted magnetic clouds [3] that thread the solar system. The kink instability is important for MHD models of astrophysical jets [4,5] and is often invoked to explain the observation of kinked structures in their synchrotron emission [6]. MHD kink modes are also observed in laboratory Z-pinch [7] and tokamak plasmas, and during spheromak formation are thought to mediate the conversion of toroidal to poloidal magnetic flux [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This code has been used to simulate AGN jets in the intracluster medium (Li et al 2006) and the Caltech plasma jet experiment (Zhai et al 2014). The spatial domain is a mesh cube with 96 grid points in each Cartesian dimension and nonreflecting outflow boundary conditions.…”
Section: Ideal Mhd Simulationmentioning
confidence: 99%